2020
DOI: 10.1002/onco.13610
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in the Management of Diffuse Large B-Cell Lymphoma in Older Patients

Abstract: Most patients with diffuse large B-cell lymphoma (DLBCL) are diagnosed at age 60 or over. Challenges to effective therapy among older individuals include unfavorable biologic features of DLBCL, geriatric vulnerabilities, suboptimal treatment selection, and toxicities of cytotoxic chemotherapy. Wider application of geriatric assessments may help identify fit older patients who benefit from standard immunochemotherapy without unnecessary dose reductions. Conversely, attenuated regimens may provide a better balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 142 publications
(244 reference statements)
2
46
0
Order By: Relevance
“…An increasing rate of population aging worldwide [39] paired with median age of onset for most hematologic malignancies in the seventh decade [40] will lead to significant growth in the number of older patients with hematologic malignancies who will require specialized care. It is increasingly well recognized that older adults with hematologic malignancies require a different approach than younger patients [41,42]. Guidance is available for treatment recommendations based on "fitness" or "candidacy for intensive treatment" though these terms are often not well defined [42,43].…”
Section: Supporting Evidence For the Role Of Multidisciplinary Care I...mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing rate of population aging worldwide [39] paired with median age of onset for most hematologic malignancies in the seventh decade [40] will lead to significant growth in the number of older patients with hematologic malignancies who will require specialized care. It is increasingly well recognized that older adults with hematologic malignancies require a different approach than younger patients [41,42]. Guidance is available for treatment recommendations based on "fitness" or "candidacy for intensive treatment" though these terms are often not well defined [42,43].…”
Section: Supporting Evidence For the Role Of Multidisciplinary Care I...mentioning
confidence: 99%
“…It is increasingly well recognized that older adults with hematologic malignancies require a different approach than younger patients [41,42]. Guidance is available for treatment recommendations based on "fitness" or "candidacy for intensive treatment" though these terms are often not well defined [42,43].…”
Section: Supporting Evidence For the Role Of Multidisciplinary Care I...mentioning
confidence: 99%
“…Three studies evaluated the diagnostic value of WB-MRI in children or young adults, while 10 studies focused on adult patients. In one study, the age of patients was not reported, and we assumed most patients to be adult since 86% (12/14) of patients were diagnosed with diffuse large B-cell lymphoma, a type of non-Hodgkin lymphoma commonly diagnosed at age over 60 (26). Five studies obtained WB-MRI with a magnetic field of 3.0 Tesla, and the remaining 9 used 1.5 Tesla.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The median age at the time of diagnosis is 66 years; furthermore, 20.1% of patients are diagnosed between 75 and 84 years of age, 25.0% between 65 and 74 years of age, and 21.2% between 55 and 64 years of age. At present, effective treatment among the elderly remains challenging owing to the adverse invasive biological characteristics of DLBCL, the baseline health status of this patient population, the late toxicity of chemotherapy, and the poor therapeutic effect of the current treatment scheme on elderly patients [8,9]. Therefore, interest in the understanding of the molecular and genetic pathways dysregulated in ageing and DLBCL has tremendously increased, along with the interest in biomarkers as a quick and quantitative measure in all areas of biomedical research.…”
Section: Introductionmentioning
confidence: 99%